Exploring Solutions for Nonlinear Fractional Differential Equations with Multiple Fractional Derivatives and Integral Boundary Conditions - Awad, Yahia (Jordan Journal of Mathematics and Statistics, 2025)
This article explores solutions for boundary value problems of nonlinear fractional differential equations with fractional integral boundary conditions. The study applies Banach’s and Krasnoselskii’s fixed point theorems to establish the existence and uniqueness of these solutions. Additionally, a practical numerical example is presented to illustrate the real-world application of the derived results. The research contributes significantly to the comprehension of boundary value problems for nonlinear fractional differential equations with fractional integral boundary conditions.